Animal Ethics and Politics Beyond the Social Contract - Reynolds, Alan (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
This paper is divided into three sections. First, I describe the wide plurality of views on issues of animal ethics, showing that our disagreements here are deep and profound. This fact of reasonable pluralism about animal ethics presents a political problem. According to the dominant liberal tradition of political philosophy, it is impermissible for one faction of people to impose its values upon another faction of people who reasonably reject those values. Instead, we are obligated to justify our political actions to each other using reasons that everyone can accept. Thus, in the second section I suggest that our condition of reasonable pluralism inspires us to turn toward some form of contractarianism. The social contract tradition emerged precisely as an attempt to think about how a society characterized by deep moral disagreement could nonetheless agree about the basic principles of justice. I will show, in this section, that although the social contract tradition would seem to contain the best tools for thinking about how to deal with moral disagreement, it fails to help us think through the important issues of animal ethics. In the concluding section, I suggest some ways in which political philosophy might move beyond contractarianism when thinking about this issue, including embracing an agonistic style of politics.